The Developmental Stage Symbionts of the Pea Aphid-Feeding Chrysoperla sinica (Tjeder) - Zhao, Chenchen; Zhao, Hui; Zhang, Shuai; Luo, Junyu; Zhu, Xiangzhen; Wang, Li; Zhao, Peng; Hua, Hongxia; Cui, Jinjie (Frontiers in Microbiology, 2019)
Chrysoperla sinica (Tjeder) is widely recognized as an important holometabolous natural enemy of various insect pests in different cropping systems, and as a non-target surrogate in environmental risk assessment of Bt rice (i.e., genetically modified rice to express a toxin gene from Bacillus thuringiensis). Like other complex organisms, abundant microbes live inside C. sinica; however, to date, microbiome composition and diversity of the whole life cycle in C. sinica has not yet been well characterized. In the current study, we analyze the composition and biodiversity of microbiota across the whole life cycle of C. sinica by using high-throughput Illumina sequencing of the 16S ribosomal RNA gene. Collectively, Proteobacteria and Firmicutes dominated the microenvironment at all stages, but their relative abundances fluctuated by host developmental stage. Interestingly, eggs, neonates, and adults shared similar microbes, including an abundance of Rickettsia and Wolbachia. After larva feeding, Staphylococcus, Enterobacteriaceae, and Serratia were enriched in larvae and pupa, suggesting food may serve as a major factor contributing to altered microbial community divergence at different developmental stages. Our findings demonstrated that C. sinica harbor a variety of bacteria, and that dynamic changes in community composition and relative abundances of members of its microbiome occur during different life cycle stages. Evaluating the role of these bacterial symbionts in this natural enemy may assist in developing environmental risk assessments and novel biological control strategies.